Effectiveness of Ethanol Extract of Aegle Marmelos Fruit Flesh on Hela Cell Apoptosis - Wulandari, Ervita Sri; Yunitama, Alifa Agil Dhillu; Futana, Ninda Pradani; Izzati, Shaula Nur; Wahyuni, Sri; Kurniawati, Yuwandira (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Background: Maja plant (Aegle marmelos) or plant commonly known as mojo, is one of the plants that contains many secondary metabolites, one of which is flavonoids. Flavonoids can be used to induce apoptosis mechanisms in cancer cells, so that specific apoptosis mechanisms in cancer cells become more effective and toxicity to normal cells is minimized. Aim: This study aims to evaluate the effectiveness of ethanol extract of maja fruit flesh (Aegle marmelos) in inducing apoptosis of HeLa cells in cervical cancer. Methodology: The method used includes ethanol extraction from maja fruit flesh and treatment of HeLa cells with various concentrations of the extract. Identification of compound content in Aegle marmelos was carried out by phytochemical tests. Apoptosis measurements were carried out using the MTT Assay method and flow cytometry analysis. Results: The results showed that 96% ethanol extract of Aegle marmelos contained secondary metabolites in the form of alkaloids, saponins, tannins, and flavonoids. The IC50 value of the MTT Assay results of maja fruit flesh extract was 7,573 µg/mL, with an apoptosis percentage of 17.6% and had an effect on inhibiting the growth of HeLa cells in the S phase as measured using the flow cytometry method. Value: The flavonoid content in 96% ethanol extract of maja fruit flesh (Aegle marmelos) has an apoptotic effect on HeLa cells. This is evidenced by the IC50 value index of 7,573 µg/mL, an apoptosis percentage of 17.6%, and the presence of inhibition in the S phase in the cell cycle.